#Sponsored #Ad: Agency Perspective on Influencer Marketing Campaigns. Issue 3 (2nd September 2019) - Childers, Courtney Carpenter; Lemon, Laura L.; Hoy, Mariea G.
Abstract: As digital and social media continue to grow in terms of usage and advertising expenditures, the advertising industry has been forced to develop innovative strategies. One such strategy is influencer marketing, which connects online personas with brands or services that target audiences trust and engage with regularly. This study provides insight into the experiences with and perceptions of influencer marketing among those working in advertising agencies. Nineteen U.S. advertising agency professionals were interviewed. Results show that the billion-dollar influencer marketing industry is largely uncharted territory that impacts strategic decision making and requires a shift in agency process for effective implementation.